HPLC-DAD-APCI-MSn analysis of the genuine carotenoid pattern of pineapple (Ananas comosus [L.] Merr.) infructescence. (January 2020) - Steingass, Christof B.; Vollmer, Kathrin; Lux, Peter E.; Dell, Carolin; Carle, Reinhold; Schweiggert, Ralf M.
Graphical abstract: Highlights: Detailed HPLC-DAD-APCI-MS n analysis of pineapple carotenoids. Identification of 21 lipophilic pigments in the pineapple infructescence. Xanthophyll esters are reported for the first time as pineapple constituents. Quantitation of carotenoids in four varieties cultivated in Ghana. Abstract: The genuine carotenoid pattern of pineapple infructescence was assessed by HPLC-DAD-APCI-MS n analysis. Prevailing pigments in the shell of 'MD2' (syn. "Extra Sweet") fruit were (all- E )-lutein and (all- E )-β-carotene, in addition to chlorophylls a and b . The edible flesh contained (all- E )-violaxanthin, (all- E )-β-carotene, and diverse esters of (9 Z )-violaxanthin with caprylic, capric, lauric, and myristic acid. The latter esters have been reported for the first time as pineapple constituents. Total carotenoid concentrations in the edible fractions of the four varieties 'Sugar Loaf', 'Smooth Cayenne', 'MD2', and 'Queen Victoria' cultivated in Ghana ranged between 29 and 565 µg/100 g of fresh weight (FW). Total carotenoids in the flesh of fully ripe 'MD2' fruit exported by air freight amounted to 302 µg/100 g of FW, those in green ripe samples dispatched by sea freight to 359–432 µg/100 g of FW. All yellow fleshed cultivars exhibited a highly similar qualitative carotenoid profile.